SrFe1-xZrxO3-δ perovskite oxides as negative electrodes for supercapacitors. (1st January 2023) - Qiao, Yin; Liu, Guanfu; Xu, Renhao; Hu, Ruiyang; Liu, Liyuan; Jiang, Guohua; Demir, Muslum; Ma, Pianpian
Abstract: Recently, perovskite oxides have been considered as promising positive electrode materials for supercapacitor applications because of their high theoretical capacitance. However, few research about using perovskite oxides as negative materials has been done up to now. Herein, a series of SrFe1- x Zr x O3-δ (0 ≤ x ≤ 0.20) oxides were synthesized as supercapacitor negative electrodes by facile solid-state reaction method for the first time. The effects on oxygen vacancies, structural stability and electrochemical performance of SrFe1- x Zr x O3-δ after Zr substituting were fully investigated. One of the key conclusions of the present study is that, introducing Zr into SrFeO3-δ results in a effective increase of oxygen vacancy, which significantly improves the charge storage capacity of the as-prepared electrode. Besides, Zr substitution is beneficial to improve the structural stability compared with pure SrFeO3-δ . It has been found that SrFe0.85 Zr0.15 O3-δ @Carbon Cloth (CC) electrode displays the best electrochemical property. At a current density of 0.5 A g −1, the electrode delivers a specific capacitance up to 163.92 F g −1, and is considered as a promising negative electrode. In addition, the maximum energy density can achieve to 7.6 Wh kg −1 at a power density of 2.0 kW kg −1 for the asymmetric supercapacitor MnO2 @CC// SrFe0.85 Zr0.15 O3-δ @CC. Overall, a certain contribution to the research and development of perovskite oxides as supercapacitornegative materials has been made in the present work. The results indicate that SrFe0.85 Zr0.15 O3-δ perovskite presents potential development prospect in the field of hybrid supercapacitor and further optimazation is expected.